PENERAPAN PENDEKATAN OPEN ENDED DALAM PEMBELAJARAN MATEMATIKA - Matondang, Khoiruddin; Saragih, Risna Mira Bella; Rina Sari (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2023)
The purpose of this study is to see the application of an open ended approach in mathematics learning in the quadrangular sub-pokok discussion in grade VII of Dwitunggal Tanjung Morawa Private Junior High School. This type of research is classroom action research. The data analysis technique in this study is using qualitative quantitative descriptive analysis methods, with the aim of finding out whether student learning outcomes have increased due to the application of the Open Ended approach. The results of this study were in the first cycle of student learning outcomes with an average score of 64.72, where only 10 students or 27.78% were completed, while 26 students or 72.22% were incomplete. Pthere is a cycle II average score of 70.41, where only 16 students or 44.45% are complete, while 20 students or 55.55% are incomplete. In system III the average score was 82.91, where student completeness increased, namely the number of students who completed learning increased to 32 students or 88.89%, while 4 students or 11,11% were incomplete.